The Persistence of Traditional Gender Roles in the Information Technology Sector: A Study of Female Engineers in India - Reena Patel and Mary Jane C. Parmentier (Information Technologies and International Development Volume 2, Number 3, Spring 2005, 29-46, 2005)
As women in India enter the rapidly expanding Information Technology (IT) workforce, it could be predicted that their active participation in this sector will change their socio-economic status within the employing organization and the communities in which they reside. It is often expected that women's participation in the professional realm will contribute to a breakdown of traditional gender roles. And indeed, the data illustrate that women are working in the IT sector in India in increasing numbers. However, datacollected in 1992 and again in 2002 by the Indian Institute of Technology suggest that not only does women's participation fail to occur at the same speed as IT expansion, but that their participation is based on a continuation of traditional gender roles, which places women on the periphery of an employing organization. Questioning the paradigm of technological determinism, this paper examines how technology and its development can adapt to the existing social structure. The persistence of such gender dividesperpetuate the notion of gender segregation and do not enhance women's socio-economic and political status, nor provide equal participation in the information economy